Assessment of the Implementation of Pakistan's National Action Plan on Antimicrobial Resistance in the Agriculture and Food Sectors - Yu Qiu; Jorge Pinto Ferreira; Riasat Wasee Ullah; Peter Flanagan; Muhammad Usman Zaheer; Muhammad Farooq Tahir; Javaria Alam; Armando E. Hoet; Junxia Song; Muhammad Akram (MDPI AG, 2024)
The agriculture and food (agrifood) sectors play key roles in the emergence, spread, and containment of antimicrobial resistance (AMR). Pakistan's first National Action Plan (NAP) on AMR was developed to guide One Health interventions to combat AMR through 2017-2022. To improve subsequent iterations, we assessed the implementation of Pakistan's NAP in the agrifood sectors (NAPag) in October 2022, using the Progressive Management Pathway on AMR tool developed by the Food and Agriculture Organization of the United Nations (FAO). The assessment tool addressed four crucial focus areas of the NAPag: governance, awareness, evidence, and practices. Each focus area contains multiple topics, which involve four sequential stages of activities to progressively achieve systematic management of AMR risk in the agrifood sectors. High-level representatives of the NAPag stakeholders provided information for the assessment through pre-event documentary review and workshop discussions. The assessment results showed that Pakistan's NAPag had an overall moderate coverage (59%) of the anticipated activities. Gaps were particularly notable in strengthening governance, good practices, and interventions in non-livestock sectors. Furthermore, only 12% of the evaluated activities were fully executed and documented, consistently remaining at the planning and piloting stages in the livestock sector across all the examined topics. Insufficient attention to non-livestock sectors, inadequate regulation and enforcement capacity, and resource constraints have hindered scalable and sustainable interventions under the current plan. This assessment provides valuable insights to strengthen the inclusiveness and contribution of the agrifood sectors in the next NAP iteration. In the short-to-medium term, strategic prioritization is necessary to optimize the use of limited resources and target the most critical gaps, such as improving awareness among key stakeholders and fortifying regulations for prudent antimicrobial use. In the long term, integration of AMR into the country's broader health, development, and agricultural transformation agendas will be needed to generate sustainable benefits.